2021
DOI: 10.55563/clinexprheumatol/pq0qp6
|View full text |Cite
|
Sign up to set email alerts
|

Pain and transition: evaluating fibromyalgia in transgender individuals

Abstract: Objective. As members of a gender minority, transgender individuals face many challenges. Many experience distress, depression, anxiety and suicidal ideation related to gender nonconformity and transphobia. Stress and trauma may contribute to the development of fibromyalgia (FM) syndrome, characterised by widespread pain and fatigue. The prevalence of FM among transgenders is not known. Methods. Transgender participants were recruited at a specialised clinic. Questionnaires included the Widespread Pain Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…However, interesting patterns are starting to emerge. 5,114,174,188 For example, Strath et al 174 found that gender identity had a stronger influence on experimental pain sensitivity than binary male/female comparisons.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…However, interesting patterns are starting to emerge. 5,114,174,188 For example, Strath et al 174 found that gender identity had a stronger influence on experimental pain sensitivity than binary male/female comparisons.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…While there are differences in pain between cis men and women, potential differences in trans individuals are much less well characterized, and systematic work is scant. Survey-based studies have suggested a higher prevalence of pain symptoms among transgender people compared to the general population ( 53 ), a difference which appears to be more pronounced for trans men as compared to cis men than between trans women and cis women ( 53 55 ). Aloisi and colleagues studied transgender women and men who had undergone hormonal treatment for at least one year, and retrospectively report whether pain had changed from before to after treatment.…”
Section: Pain In Relation To Gender Identitymentioning
confidence: 99%
“…Conversely, a questionnaire-based study of 26 trans men found that 60% reported a significant improvement in chronic headache symptoms that had been present prior to the start of testosterone treatment ( 55 ). Meanwhile, a study of Israeli trans men did not find a significant difference between the prevalence of fibromyalgia symptoms before and after the initiation of hormonal therapy ( 53 ). A U.S. survey-based study of 100 trans men who had undergone phalloplasty and who were taking testosterone found that 51% (48/94) reported pain with sexual penetration.…”
Section: Hormone Replacement Therapy (Hrt) In Adultsmentioning
confidence: 99%
“…3 However, as research with gender and sexual minorities has increased, data suggest that higher rates of chronic pain syndromes are observed in sexual minority (SM, persons who are gay, lesbian, bisexual, or have other non-heterosexual sexual orientations) and gender minority (GM, persons with a gender identity or expression that is different than that traditionally expected based on the sex they were assigned at birth) populations compared to heterosexual and cisgender populations. [4][5][6] The goal of the present study was to identify and characterize the presence and characteristics of chronic pain in SM and GM persons using data from The PRIDE Study, which is the first large-scale, long-term national cohort health study of people who identify as lesbian, gay, bisexual, transgender, queer (LGBTQ+), or as another sexual or gender minority person.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, as research with gender and sexual minorities has increased, data suggest that higher rates of chronic pain syndromes are observed in sexual minority (SM, persons who are gay, lesbian, bisexual, or have other non-heterosexual sexual orientations) and gender minority (GM, persons with a gender identity or expression that is different than that traditionally expected based on the sex they were assigned at birth) populations compared to heterosexual and cisgender populations. 4-6…”
Section: Introductionmentioning
confidence: 99%